Host‐Guest Strategy Enabling Nonhalogenated Solvent Processing for High‐Performance All‐Polymer Hosted Solar Cells. Issue 9 (14th March 2023) - Huang, Yuting; Chen, Haiyang; Fan, Qunping; Chen, Ziyuan; Ding, Junyuan; Yang, Heyi; Sun, Zhe; Zhang, Rui; Chen, Weijie; Yang, Changduk; Gao, Feng; Li, Yaowen
Comprehensive Summary: The power conversion efficiencies (PCEs) of all‐polymer solar cells (all‐PSCs), usually processed from low‐boiling‐point and toxic solvents, have reached high values of 18%. However, poor miscibility and uncontrollable crystallinity in polymer blends lead to a notable drop in the PCEs when using green solvents, limiting the practical development of all‐PSCs. Herein, a third component (guest) BTO was employed to optimize the miscibility and enhance the crystallinity of PM6/PY2Se‐F host film processed from green solvent toluene ( TL ), which can effectively suppress the excessive aggregation of PY2Se‐F and facilitate a nano‐scale interpenetrating network morphology for exciton dissociation and charge transport. As a result, TL ‐processed all‐polymer hosted solar cells (all‐PHSCs) exhibited an impressive PCE of 17.01%. Moreover, the strong molecular interaction between the host and guest molecules also enhances the thermal stability of the devices. Our host‐guest strategy provides a unique approach to developing high‐efficiency and stable all‐PHSCs processed from green solvents, paving the way for the industrial development of all‐PHSCs. Abstract : BTO as a guest component was added into all‐polymer PM6/PY2Se‐F systems to improve the miscibility of donor/acceptor, thus suppressing the excessive aggregation of PY2Se‐F in green solvent toluene ( TL ). In addition, BTO can induce PY2Se‐F to form a preferred face‐on orientation, which is a benefit in forming a nano‐scale interpenetrating network morphology with improved stability. As a result, TL ‐processed all‐polymer hosted solar cells based on PM6/PY2Se‐F:0.2 BTO delivered a maximum PCE of 17.01%.